The Existence and Effectiveness of Price Support Activities in Germany: A Note - Andreas Oehler; Marco Rummer; Peter N. Smith (Otto-Friedrich-Universität Bamberg, Lehrstuhl für Betriebswirtschaftslehre, insbesondere Finanzwirtschaft, 2004)
The overallotment or greenshoe option has become very popular in the German IPO market since its introduction in 1995 and is nowadays an important tool to stabilize IPOs or to issue additional shares in the case of excess demand. Besides providing evidence for the prevalence of price support activities by the underwriter we show that the greenshoe option which seems to be used to support overpriced offerings in the secondary market is not very effective in propping up aftermarket prices. Additionally, the market seems to decide quite early which firms are ?losers? and which are ?winners? in terms of stock market performance.
Keywords: G12; G10; G32; G24; 330; Initial Public Offerings (IPO); Price Support; Overallotment Option